2021
DOI: 10.1152/ajprenal.00507.2020
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin type 2 receptor activation limits kidney injury during the early phase and induces Treg cells during the late phase of renal ischemia

Abstract: Kidney infiltrating immune cells such as monocytes, neutrophils, and T-cells play critical roles in renal ischemia-reperfusion (IR) injury and repair. Recently, angiotensin AT2R has been implicated in protecting kidneys against injury and monocyte infiltration, particularly in chronic kidney disease. However, the role of AT2R in IR injury and repair phases and T-cell modulation is unknown. To address this question, Sprague-Dawley (SD) rats were subjected to IR+/-AT2R agonist C21 treatment. IR caused an early (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…Additionally, resident macrophages are also present in the kidney (Munro and Hughes, 2017). Our work and previous literature has suggested the involvement of proximal tubular epithelial cells (Dhande et al, 2013), macrophages (Dhande et al, 2015), T-cells (Curato et al, 2010;Skorska et al, 2015), dendritic cells (Ma et al, 2019) and Treg cells (Ali et al, 2021) as a source of IL-10 upon AT2R stimulation. This could be responsible for higher concentrations of renal IL-10 as compared to plasma.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Additionally, resident macrophages are also present in the kidney (Munro and Hughes, 2017). Our work and previous literature has suggested the involvement of proximal tubular epithelial cells (Dhande et al, 2013), macrophages (Dhande et al, 2015), T-cells (Curato et al, 2010;Skorska et al, 2015), dendritic cells (Ma et al, 2019) and Treg cells (Ali et al, 2021) as a source of IL-10 upon AT2R stimulation. This could be responsible for higher concentrations of renal IL-10 as compared to plasma.…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, another set of animals were treated with the same regimen and euthanized 24 h after LPS treatment (Protocol 4). Renal functional indices BUN and creatinine, and tubular injury are early diagnostic markers for AKI (Basile et al, 2012;Fattah and Vallon, 2018) and the protective role of AT2R against IR-induced AKI has been demonstrated in another study in our laboratory (Ali et al, 2021). In view of the findings from our laboratory in I/R and LPS models of AKI, the levels of BUN and urinary creatinine were again measured in the 24-h samples.…”
Section: Discussionmentioning
confidence: 83%
“…Renin-angiotensin system is an important hormonal system involved in regulating renal structure and function, of which abnormal activation triggers the deleterious effects of angiotensin II [ 29 ]. As a component of the renin-angiotensin system, angiotensin type 2 (AT 2) receptor (AT2R) is believed to be renoprotective by functionally antagonizing the proinflammatory actions of angiotensin II, rendering to protecting organs from injury, including AKI [ 30 , 31 ]. Given the close relationship between AT2R and IL-10 has been reported in various research on renal diseases, we wonder whether the renoprotective function of IL-10 is associated with AT2R.…”
Section: Discussionmentioning
confidence: 99%
“…We found that C21 raises the numbers of CD4 + CD25 + FoxP3 + T cells in CIA, a fact that likely contributed to the improvement of arthritis. Recently, Hussain et al showed protective effects of C21 on kidney ischemia by modulation of CD4 T cells towards the regulatory T cell phenotype (79).…”
Section: Discussionmentioning
confidence: 99%